Taking Stock, July 2017 : An Update on Vietnam’s Recent Economic Developments - World Bank (World Bank, Hanoi, 2017)
A broad-based recovery in global economic activity has been taking hold since late 2016. Industrial production has picked up and global trade accelerated after two years of pronounced weakness. A gradual recovery in commodity prices diminished growth constraints among commodity exporters, including major emerging economies. Despite heightened policy uncertainty, growth in major advanced economies, including the United States, the European Union, and Japan, has strengthened, reflecting buoyant domestic demand and rising exports. Growth in developing East Asia and Pacific (EAP) continues to be resilient as already robust domestic demand was supported by a pickup in external demand and a gradual recovery in commodity prices. After a large surplus in 2016, Vietnam’s external current account balance started to decline in early 2017. Robust growth in exports, tourism receipts, and private remittances led to a current account surplus of about 4 percent of GDP in 2016, marking the sixth consecutive year of a widening current account surplus. The financial account also saw large net inflows of foreign direct investment (FDI) and long-term loans, allowing the State Bank of Vietnam to gradually rebuild foreign reserves. The current account surplus started to decline in early 2017 due to a recovery in import growth. Bolstered by a strong external position, the nominal exchange rate has been relatively stable but the real exchange rate continues to appreciate. The reference rate was devalued modestly by 1.23 percent in 2016 and around 1.3 percent year-to-date in 2017. Meanwhile, the real effective exchange rate continued to appreciate by about 5 percent in 2016 and 24 percent since 2010. Real exchange rate appreciation is driven by a large external surplus of the FDI sector, but is a concern for Vietnam’s domestic private enterprises, which continue to face significant external imbalance and competitiveness challenges. This special focus issue is part of two-part series on fiscal reforms. While this installment of the taking stock special topic is focused on specific revenue and debt management options to underpin more sustainable and efficient fiscal management, the December issue will focus on expenditure restructuring.